EFFECTIVE TEACHING OF ENGLISH IN DISTANCE LEARNING CONDITIONS: LEADING PRINCIPLES AND PRACTICAL SKILLS - o‘g‘li, Ismoilov Javohir Alisher (Research Focus International Scientific Journal, 2026)
This article analyzes effective methods of teaching English in a distance learning environment, as well as the role of modern pedagogical approaches and digital technologies. It also highlights ways to enhance students’ motivation in language learning and to create an interactive learning environment.